Servant leadership and its association with an environment of empathic care: an empirical analysis of the perspectives of mid-level practitioners. Issue 1 (4th November 2021) - Silver, Reginald; Martin, Mark
Abstract : Purpose: At the nexus of servant leadership and empathic care, this paper aims to explore the perceptions that mid-level practitioners express regarding the role that servant leadership plays in fostering an environment of empathic care. Design/methodology/approach: The authors surveyed mid-level practitioners across a large integrated health system ( n = 167). Through exploratory factor analysis, we identify factors that serve as antecedents to an environment of empathic care. The factor analysis was complimented with partial least squares structural equation modeling to test a theoretical model of empathic care. Findings: The model explains approximately 37% of the variance observed in an empathic care environment ( R 2 = 0.372). The authors identify key constructs within servant leadership that health-care leaders can focus their efforts on to promote an environment of empathic care. Originality/value: This study answers multiple calls for more empirical research into servant leadership and is one of the few studies that explores servant leadership within an exogeneous context. This research focuses on the perceptions of mid-level providers, whereas most extant servant leadership and empathy research focuses on the perceptions of patients. The authors extend servant leadership theory in a health-care context and support prior findings that servant leadership is a multidimensional construct. The authors outline a sound methodological approach for investigating the linkage between specific principles of servant leadership that can serve as predictors for the creation of an environment of empathic care.